Synergistic potential of teriflunomide with fluconazole against resistant Candida albicans in vitro and in vivo - Li, Xiuyun; Kong, Bing; Sun, Yaqiong; Sun, Fenghua; Yang, Huijun; Zheng, Shicun (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Candida albicans is the primary cause of systemic candidiasis, which is involved in high morbidity and mortality. Drug resistance exacerbates these problems. In addition, there are limited antifungal drugs available. In order to solve these problems, combination therapy has aroused great interest. Teriflunomide is an immunosuppressant. In the present work, we aimed to identify whether teriflunomide can reverse the resistance of Candida albicans in the presence of sub-inhibitory concentrations of fluconazole in vitro and in vivo. Methods Seven Candida albicans isolates were used in this study. Susceptibility of Candida albicans in vitro to the drugs was determined using a checkerboard microdilution assay in accordance with the recommendations of the Clinical and Laboratory Standards Institute. The effects of drugs on biofilm biomass of Candida albicans were determined by crystal violet staining. The development ability of Candida albicans hyphae was performed using a modified broth microdilution method. Galleria mellonella was used for testing the in vivo efficacy of the combination therapies. Results We found that the combination of teriflunomide (64 µg/mL) and fluconazole (0.5-1 µg/mL) has a significant synergistic effect in all resistant Candida albicans isolates (n=4). Also, this drug combination could inhibit the immature biofilm biomass and hyphae formation of resistant Candida albicans. Galleria mellonella was used for testing the in vivo efficacy of this combination therapies. As for the Galleria mellonella larvae infected by resistant Candida albicans, teriflunomide (1.6 µg/larvae) combined with fluconazole (1.6 µg/larvae) significantly increased their survival rates, and reduced the fungal burden, as well as damage of tissue in comparison to that in the control group or drug monotherapy group. Conclusion These results expand our knowledge about the antifungal potential of teriflunomide as an adjuvant of existing antifungal drugs, and also open new perspectives in the treatment of resistant Candida albicans based on repurposing clinically available nonantifungal drugs.